Spiritual Emotional Freedom Technique for Enhancing the Meaning of Life in Patients with Ischemic Stroke - Dedek Saiful Kohir; Agilia Nur Fauziah; Sulastri Sulastri; Almurhan Almurhan; Sunarsih Sunarsih; Siti Fatonah (Poltekkes Kemenkes Tanjung Karang, 2026)
Beyond its effects on physical motor abilities, ischemic stroke frequently results in psychological and spiritual crises. Loss of